Developing and testing a structured visual skills screening tool for use in sports vision training: an exploratory study with field hockey participants - Wimshurst, Z. L.; Sowden, P. T. (Asian Journal of Sport and Exercise Psychology, 2025)
The field of sports vision is becoming increasingly popular with more research and a rise in practitioners aiming to improve the performance of athletes through training their visual skills. However, whilst it has been suggested that different sports have different visual requirements, there is no easy way to screen for these without having to rely on extensive testing of the visual abilities of elite athletes within the sport, which is often not a practical option. Consequently, in this paper, we designed and tested a screening questionnaire to elicit visual skills information from experts within the sport of field hockey in a quick and easily applicable manner. Descriptions of 23 visual skills were rated on a 5-point Likert scale by 481 participants to show how important they are perceived to be for field hockey players. All participants were involved in field hockey as players, coaches, or umpires. The same questionnaire was completed at a second time point by 129 of the original respondents to assess stability over time. Principal components analysis showed that the 23 visual skills loaded onto four visual skillsets. The perceived importance of these differed, with a perception that skills associated with visual interception and spatial positioning are more important than skills associated with maintaining focus on and recognising visual objects. Our findings suggest that the tool could be useful both to guide the focus of visual skills research in different sports and as a practical aid to coaches looking to systematically select the focus of visual skills training for their players.